2014
DOI: 10.1177/0960327114538987
|View full text |Cite
|
Sign up to set email alerts
|

Zingiberene attenuates hydrogen peroxide-induced toxicity in neuronal cells

Abstract: In this experimental design, we explored the neuroprotective potential of zingiberene (ZGB), a monocyclic sesquiterpene, in hydrogen peroxide (H2O2)-induced toxicity in newborn rat cerebral cortex cell cultures for the first time. The rats were exposed to H2O2 for 6 h to determine the oxidative stress levels. To evaluate cell viability, both 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyltetrazolium bromide and lactate dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Zingiberene, the chief component of the Z. officinale essential oil here analyzed, is a monocyclic sesquiterpene hydrocarbon with natural antioxidant and cytotoxic activities: it is capable of protecting against H 2 O 2 -induced cytotoxicity and oxidative DNA damage in neuronal cells [35] as well as inhibiting the growth of lymphocytic cells in a dose-dependent manner [36]. Furthermore, high zingiberene content in tomato plants provides resistance against arthropod pests including spider mite ( Tetranychus urticae ) and whitefly ( Bemisia tabaci ) [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…Zingiberene, the chief component of the Z. officinale essential oil here analyzed, is a monocyclic sesquiterpene hydrocarbon with natural antioxidant and cytotoxic activities: it is capable of protecting against H 2 O 2 -induced cytotoxicity and oxidative DNA damage in neuronal cells [35] as well as inhibiting the growth of lymphocytic cells in a dose-dependent manner [36]. Furthermore, high zingiberene content in tomato plants provides resistance against arthropod pests including spider mite ( Tetranychus urticae ) and whitefly ( Bemisia tabaci ) [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…For example, high levels of ROS-mediated oxidative stress can damage the structure and functions of endothelial cells, and contribute to pathogenesis of hypertension, diabetes, inflammation and atherosclerosis [ 58 , 59 ]. The assays of H 2 O 2 -induced death of endothelial cells or neuronal cells are commonly used in vitro models for determining antioxidant effects on oxidative stress [ 31 , 32 , 60 , 61 ]. Using these assays, other have shown that H 2 O 2 is highly permeable to cell membrane [ 62 ] and can increase production of O 2 − by activating NADPH oxidase and eNOS uncoupling [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TOS assay was calibrated using H 2 O 2 , and the results are presented as µM H 2 O 2 equivalent per liter. The automated TAC and TOS assays were performed using commercially available kits (n = 5) (Rel Assay, Gaziantep, Turkey) [21,22].…”
Section: Tac and Tos Analysismentioning
confidence: 99%